Faktor Determinan Stock Buyback (Studi Perusahaan di Pasar Modal Indonesia Periode 2012-2020) - Yuliana, Yuliana; Susi, Susi; Syaipudin, Usep (E-Jurnal Akuntansi; Vol 32 No 4 (2022), 2022)
The purpose of this study is to determine whether the influence of undervaluation and free cash flow has an influence on the stock repurchase policy. This study uses companies that carry out stock buybacks from 2012-2020 listed on the Indonesia Stock Exchange as the population in this study. The method of determining the sample using purposive sampling technique. The number of research samples is 55 companies that repurchase shares with an 8-year observation period, resulting in 83 observational data. The hypothesis in this study was tested using multiple linear regression analysis techniques. The results of the analysis show that the undervaluation proxied by the Market to Book Ratio has a positive effect on the stock buyback policy. Meanwhile, free cash flow has a negative effect on the stock repurchase policy. Keywords: Stock Buyback; Undervaluation; Free Cash Flow.